Influence of insulin antibodies on pharmacokinetics and bioavailability of recombinant human and highly purified beef insulins in insulin dependent diabetics. Issue 6483 (8th June 1985) - Gray, R S; Cowan, P; di Mario, U; Elton, R A; Clarke, B F; Duncan, L J
Abstract : Sixteen insulin dependent diabetics of long standing, with undetectable fasting plasma C peptide concentrations, and eight non-diabetic controls were each infused intravenously with biosynthetic human and highly purified beef insulin (1 mU/kg/min) while euglycaemia was maintained by a Biostator. No difference was observed between the two insulins in respect of insulin pharmacokinetics or biological action. The diabetics showed appreciable insulin resistance, manifested by a 40% reduction in the rate of insulin mediated glucose disposal, which was unrelated to the presence of insulin antibodies. Insulin binding antibodies, however, increased insulin's clearance rate and distribution space and prolonged its pharmacological and biological half lives. The rate at which insulin action was lost, after an intravenous infusion, was more rapid in diabetics without insulin antibody binding than in controls. In respect of their influence on insulin pharmacokinetics, moderate concentrations of insulin antibodies may be of positive advantage to all diabetics without endogenous insulin secretion and are not responsible for the insulin resistance of type 1 diabetes.